ChemInform Abstract: Site Preference and Ordering Induced by Au Substitution in the γ‐Brass Related Complex Au—Cr—Zn Phases. Issue 27 (13th June 2013) - Jana, Partha P.; Henderson, Ryan; Harbrecht, Bernd; Lidin, Sven
Abstract A series of samples of (AuxCr1‐x)Zn≈17 (0.02 ≤ x ≤ 0.1) is prepared by solid state reaction of the elements (fused silica ampules, argon; 1.